2008
DOI: 10.3201/eid1410.080119
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Interactions during Upper Respiratory Tract Infections

Abstract: Competitive interactions between bacteria differ by number and species present; thus, vaccination and treatment strategies may alter nasopharyngeal flora and disease susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
143
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(160 citation statements)
references
References 36 publications
(61 reference statements)
14
143
2
1
Order By: Relevance
“…S. aureus and S. pneumoniae is negatively correlated in the nasopharynx (Bogaert et al, 2004). However, whereas Streptococcus species are dominant in the nasopharynx (Pettigrew et al, 2008) and various skin habitats (Gao et al, 2007;Fierer et al, 2008), this study shows that they are only in low abundance in the anterior nares, a feature also supported by previous culture-dependent studies (Lina et al, 2003).…”
Section: Discussionsupporting
confidence: 86%
“…S. aureus and S. pneumoniae is negatively correlated in the nasopharynx (Bogaert et al, 2004). However, whereas Streptococcus species are dominant in the nasopharynx (Pettigrew et al, 2008) and various skin habitats (Gao et al, 2007;Fierer et al, 2008), this study shows that they are only in low abundance in the anterior nares, a feature also supported by previous culture-dependent studies (Lina et al, 2003).…”
Section: Discussionsupporting
confidence: 86%
“…pneumoniae, H. influenzae, M. catarrhalis and Staph. aureus in healthy children was analysed using a logistic regression model (Pettigrew et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, some carriage studies have reported the cooccurrence of a number of bacteria and suggested direct interactions such as interference or competition between the various bacterial species in the URT (Jacoby et al, 2007;Pettigrew et al, 2008). Although knowledge is limited, a change of colonization pattern of potential pathogens in the URT may have an effect on both the development of disease and the spread of pathogens in an individual.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of tympanocentesis over 4 respiratory tract illness seasons in a private practice, the percentage of 128 Data show that nasopharyngeal colonization of children vaccinated with PCV7 increasingly is caused by S pneumoniae serotypes not contained in the vaccine. [129][130][131][132] With the use of the recently licensed 13-valent pneumococcal conjugate vaccine (PCV13), 133 the patterns of nasopharyngeal colonization and infection with these common AOM bacterial pathogens will continue to evolve.…”
Section: Microbiologymentioning
confidence: 99%